2014
DOI: 10.1002/art.38614
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular Sprifermin (Recombinant Human Fibroblast Growth Factor 18) in Knee Osteoarthritis: A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: Objective. To evaluate the efficacy and safety of intraarticular sprifermin (recombinant human fibroblast growth factor 18) in the treatment of symptomatic knee osteoarthritis (OA).Methods. The study was a randomized, doubleblind, placebo-controlled, proof-of-concept trial. Intraarticular sprifermin was evaluated at doses of 10 g, 30 g, and 100 g. The primary efficacy end point was change in central medial femorotibial compartment cartilage thickness at 6 months and 12 months as determined using quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
177
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 48 publications
10
177
0
5
Order By: Relevance
“…Fgf18 also promotes chondrogenesis, chondrocyte proliferation and cartilage regeneration in surgically induced models of osteoarthritis (31,32,43,(52)(53)(54)(55)(56). In clinical trials, intra-articular injections of recombinant Fgf18 resulted in dose-dependent increases in total cartilage content, even though thickness of the central medial femorotibial compartment cartilage was unchanged (57). Thus, the effects of Fgf18/Fgfr signaling are complex and may be temporally and spatially controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Fgf18 also promotes chondrogenesis, chondrocyte proliferation and cartilage regeneration in surgically induced models of osteoarthritis (31,32,43,(52)(53)(54)(55)(56). In clinical trials, intra-articular injections of recombinant Fgf18 resulted in dose-dependent increases in total cartilage content, even though thickness of the central medial femorotibial compartment cartilage was unchanged (57). Thus, the effects of Fgf18/Fgfr signaling are complex and may be temporally and spatially controlled.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-18 via FGFR3 also protects against loading-induced damage in cartilage explants ex vivo [130] and intraarticular administration of FGF18 protects against cartilage damage in a rat model of injury-induced arthritis [131] Thus, there is considerable interest in the potential of anabolic factors such as FGF-18 for enhancing cartilage regeneration with tissue engineering approaches [132]. However a recent proof-of-concept trial with human recombinant FGF-18, sprifermin, showed statistically significant dose-dependent improvement in pre-specified secondary structural end points by MRI, radiographic joint space narrowing, and WOMAC pain scores [133]. …”
Section: Cartilage Anabolism and Tissue Engineering Strategiesmentioning
confidence: 99%
“…In a rat model of OA, intra-articular injections of sprifermin induced a signifi cant, dosedependent reduction in cartilage degeneration. In a recent clinical study, sprifermin had no effect on medial femorotibial compartment cartilage volume, although it did signifi cantly and dose dependently reduce the loss of total and lateral femorotibial compartment cartilage volume [ 82 ]. In stark contrast to the situation in RA, where there is almost an embarrassment of riches when it comes to both biologics and small-molecule targeted therapy, the search for a disease-modifying antiosteoarthritis drug has thus far ended in disappointment, with a number of promising drug candidates failing clinical trials.…”
Section: 3mentioning
confidence: 97%